The Post-traumatic Stress Disorder in COVID-19 Recovered Patients: A Cross-sectional Study - Elham Khadem Hamzeii; Zahra Mortazavi; Roya Najafivosough; Hojjat Allah Haghgoo; Saideh Sadat Mortazavi (University of Social Welfare and Rehabilitation Sciences, 2023)
Objective Post-traumatic stress disorder (PTSD) is one of the anxiety disorders caused by a specific event, which can be catastrophic events (natural disasters, war, imprisonment in a forced labor camp) or everyday adversities (death of relatives, divorce, carrying bags). Since patients who have recovered from COVID-19 are exposed to such events, this research was conducted to determine the prevalence of PTSD in this group. Materials & Methods This study was cross-sectional. The statistical population included all patients who recovered from COVID-19 between November 2021 and February 2022 in Hamedan City, Iran; based on Krejcie and Morgan's sample size table, 185 patients were selected by simple random sampling method. The research tool was the demographic questionnaire and the Mississippi post-traumatic stress disorder questionnaire (Mississippi PTSD); the data were analyzed using the Mann-Whitney and Kruskal-Wallis tests. Results The results showed that the Mean±SD score of PTSD was 80.37±17.37 in the subjects who recovered from COVID-19. The relationship between the demographic variables of gender (P=0.01), education (P=0.039), occupation (P=0.24), marriage (P=0.62), age (P=0.048), weight (P=0.047), height (P=0.023) with PTSD were reported. Conclusion The results showed that 76.2% of people who recovered from COVID-19 were exposed to PTSD with moderate and high severity; therefore, techniques to reduce anxiety from the coronavirus are recommended.